“You can be connected all the time”: the use of smartphones by brazilian university students and sociabilities - Elesbão Sbrissa, Luiza (2020)
The use of smartphones in the sociability networks of brazilian university students living in a student residence is analyzed. A field research was carried out with participant observation, notes in field diaries and dialogical encounters. The material was analyzed under Social Psychology and Material Culture Studies. The uses of smartphones maintain and reinvent sociability practices, turning them into artefacts of “physical-affective communication”. In addition, they participate in the emancipation process and produce an extension of cyber-holding in youth, facilitating adaptation of life to university. On the other hand, the sense of attachment to smartphones causes tensions between their sociability networks and generates anxiety.